2007
DOI: 10.1258/095646207782212289
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of nevirapine-associated skin rashes among HIV-infected patients with CD4 cell counts <250 cells/μL

Abstract: The objective of the study was to determine cumulative incidence and risk factors of nevirapine (NVP)-associated rashes that lead to NVP discontinuation among HIV-infected patients with CD4 <250 cells/microL. A retrospective cohort study was conducted among antiretroviral-naïve HIV-infected patients who had baseline CD4 <250 cells/microL and were initiated NVP-based antiretroviral therapy (ART) between January 2003 and October 2005. There were 910 patients with a mean age of 35.4 years and 43% were women. Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
5
16
1
Order By: Relevance
“…An association between baseline CD4 count and severe skin reactions due to nevirapine has been found previously . We found no association between CD4 count and severe skin reactions, possibly due to relatively low baseline CD4 counts across both cases and controls.…”
Section: Discussionsupporting
confidence: 69%
“…An association between baseline CD4 count and severe skin reactions due to nevirapine has been found previously . We found no association between CD4 count and severe skin reactions, possibly due to relatively low baseline CD4 counts across both cases and controls.…”
Section: Discussionsupporting
confidence: 69%
“…No association between gender and CD4 cell count and risk of NVP-associated rash were observed in the present study even though these two factors were consistently reported in some studies [11-16]. We did not find any association between gender and risk of rash in our previous study using the same cohort [15].…”
Section: Discussioncontrasting
confidence: 71%
“…Rare but serious hypersensitivity reactions, Stevens-Johnson Syndrome and toxic epidermal necrolysis, had been reported [5, 9, 10]. Risk factors for NVP-associated rash were female gender including pregnant women [11-14], lower body weight [15], initiation of NVP at high CD4 cell counts [11, 12, 15, 16], pretreated with antiretroviral drugs less than 12 months [17], higher plasma NVP level [17], and genetic (human leukocyte antigen) [18, 19]. However, some factors may not be applicable to patients who were initiated NVP at low CD4 cell counts in resource-limited settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, starting the switch with the full dose could increase the risk of adverse effects (including skin rash). However, if switching patients to nevirapine they should have an appropriate CD4 cell count, which should decrease the risk of skin rash [33]. Table 2 Maraviroc simulated average pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%